A novel method to determine the formaldehyde emission characteristic parameters of building materials at multiple temperatures. (February 2019) - Zhou, Xiaojun; Liu, Yanfeng; Song, Cong; Wang, Xinke; Wang, Fenghao; Liu, Jiaping
Abstract: Formaldehyde emissions of building materials are greatly influenced by the indoor air temperature. An accurate evaluation of the influence of formaldehyde emissions on indoor air quality requires an investigation of the emission characteristic parameters at different temperatures. Based on the adsorption potential theory, this paper derived the correlation between the initial emittable concentration ( C 0 ) and the partition coefficient ( K ) of formaldehyde emissions from building materials. On account of the characteristics of a high equilibrium concentration of formaldehyde emissions under high temperatures in an airtight environment, a step temperature rising emission (STRE) method to simultaneously determine the characteristic parameters of formaldehyde emissions at multiple temperatures was proposed. This innovative method was validated by theoretical models in the literature and via independent experiments. In addition, an optimization method for determining the appropriate volumetric air/material phase ratio was discussed and analyzed to improve the accuracy and reliability of the STRE method. This method aims to improve the measurement efficiency of the emission characteristic parameters and provides inspiration for evaluating the hazard posed by formaldehyde emissions from furniture and building materials. Graphical abstract: Image 1 Highlights: The correlation between C 0 and K is derived based on adsorption potential theory. The STRE method is proposed to efficiently determine the characteristic parameters. Hazard of formaldehyde emissions at multiple temperatures can be quick predicted. The reliability of the STRE method is comprehensively verified.